Tenancy Sustainment Team health research: morbidity and mortality amongst people with experience of rough sleeping: Findings report - Cornes, Michelle; Rice, Becky; Shulman, Caroline; Hudson, Briony (King's College London, 2019)
This report presents the key findings of a small-scale research project exploring the mortality and health needs of clients of Tenancy Sustainment Team (TST) services. The research was commissioned in response to concerns by the Greater London Authority (GLA) and TST service managers about premature deaths among TST clients and the need to learn more about the health needs of this group, particularly the incidence of chronic or long-term health conditions (LTCs).